Knock, knock. Who's there? A Translation and Study of Þóruljóð - Stewart, Anna Alexandra McCully, 1994- (2017)
There is a great deal of long-neglected late- or post-medieval Icelandic literature which has only recently begun to receive scholarly attention. This includes the genre of poems known as sagnakvæði, eight long, narrative poems written in Eddic metre which were written down in the seventeenth century and onwards. However, there is much evidence to suggest that they were composed centuries previously and had circulated in oral transmission for some time. This thesis will outline the preservation and transmission of the sagnakvæði and provide an overview of the existing scholarly research into the poems. The thesis will then focus on one of the sagnakvæði, Þóruljóð, which tells of a young Danish leader named Þorkell and a giantess named Þóra who appears suddenly at his farmstead at Christmas and asks for lodgings. I have produced the first English translation and in-depth of Þóruljóð, as well as a discussion of possible sources and analogues for the poem and its titular character Þóra. This includes a discussion of the medieval Icelandic vikivaki games, group entertainments played at dance-gatherings at Icelandic farmsteads involving costumed figures, such as Háu-Þóruleikur, the central figure in which bears a distinct similarity to the character of Þóra. Relevant figures in folklore, Eddic poetry and sagas are also discussed. In doing so, I hope to place the poem into its wider literary and cultural context and demonstrate the interplay between different types of literature and folk-tales in medieval Iceland. Til er fjöldinn allur af íslenskum bókmenntum frá síðmiðöldum og frá því eftir siðaskipti, sem hingað til hafa fengið litla sem enga fræðilega umfjöllun. Þetta á meðal annars við um kvæði sem nefnast sagnakvæði, sem eru átta löng frásagnarkvæði með fornyrðislagi sem voru skráð á 17. öld og síðar. Ýmislegt bendir þó til þess að kvæðin hafi verið samin vel fyrir þann tíma og varðveist í munnlegri geymd þar til þau voru skráð í núverandi formi. Í ritgerðinni er gerð grein fyrir varðveislu og útbreiðslu ...